2017
DOI: 10.1136/jmedgenet-2016-104468
|View full text |Cite
|
Sign up to set email alerts
|

STAG1mutations cause a novel cohesinopathy characterised by unspecific syndromic intellectual disability

Abstract: We report an international series of 17 individuals from 16 families presenting with syndromic unspecific ID that could be attributed to a deletion or point mutation. This first series reporting the phenotype ascribed to mutation in highlights the importance of data sharing in the field of rare disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 38 publications
3
36
1
Order By: Relevance
“…In the second category, we identified several interesting candidate genes including a de novo deletion including STAG1 and a de novo intragenic duplication in FGF12 . In both genes, only recently have pathogenic SNVs been reported in patients with neurodevelopmental disorders including epilepsy . We further identified a deletion including SETBP1 associated with Shinzel‐Gieidon syndrome and ID (OMIM 611060) and a duplication including HCN2, a gene in which SNVs exerting a gain‐of‐function effect have recently been suggested as a risk factor for genetic generalized epilepsies .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In the second category, we identified several interesting candidate genes including a de novo deletion including STAG1 and a de novo intragenic duplication in FGF12 . In both genes, only recently have pathogenic SNVs been reported in patients with neurodevelopmental disorders including epilepsy . We further identified a deletion including SETBP1 associated with Shinzel‐Gieidon syndrome and ID (OMIM 611060) and a duplication including HCN2, a gene in which SNVs exerting a gain‐of‐function effect have recently been suggested as a risk factor for genetic generalized epilepsies .…”
Section: Resultsmentioning
confidence: 91%
“…The patient in this study only showed severe epilepsy and ID, suggesting that the SETBP1 ‐mutation phenotype may be broader than previously described. One patient had a microdeletion, classified here as possibly pathogenic, which includes STAG1 , now linked with epilepsy as a cohesinopathy, and one patient carried a de novo intragenic duplication in FGF12 in which SNVs have recently been reported in patients with epileptic encephalopathies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The convergent molecular pathogenesis of CHOPS and CdLS is evidenced by a similar pattern of dysregulated genes . Combined microarray and gene panel/WES/WGS disclosed the Xq25 microduplication syndrome where a copy number gain of STAG2 alone is responsible for the phenotype and the syndromic unspecific ID due to STAG1 mutation or microdeletion …”
Section: Dd/id Syndromes Caused By Defects In Chromatin Architecturalmentioning
confidence: 99%
“…Amongst all cohesin subunits and cofactors, SA2 is the one most frequently mutated in different cancer types, such as urothelial bladder carcinoma (26% of tumor samples) (Balbas-Martinez et al 2013;Solomon et al 2013), Ewing sarcoma (15-22% of tumor samples) (Brohl et al 2014;Tirode et al 2014) and or acute myeloid leukemia (6% of tumor samples) (Rocquain et al 2010). Interestingly, congenital loss-of-function mutations in SA1 and SA2 do not cause Cornelia de Lange syndrome (CdLS), the major syndrome linked to mutations in core cohesin components and co-regulators, but rather associate with developmental delay and various malformations (Lehalle et al 2017;Mullegama et al 2017;Soardi et al 2017).…”
Section: Introductionmentioning
confidence: 99%